SCENARIO FERDY SAMBO ORDERS TO KILL BRIGADIR JOSHUA MAINTAINING FAMILY DIGNITY, EXECUTIONS, OR MOTIVES - Junaedi, Junaedi; Yusuf, Anas; Hidayat, Rumanul (IJBLE Scientific Publications Community Inc., 2023)
The president also reminded the National Police to reveal the case of Brigadier J as it is. This, said Jokowi, is to maintain the image of Polri in the eyes of the public. National Police Chief Gen. Pol. Listyo Sigit Prabowo confirmed that there was no shooting incident in the case of Brigadier J's death. Based on the results of the work of the special team, it is known that Bharata E allegedly shot Brigadier J on orders from Inspector General Ferdi Sambo alias FS. Then it was engineered that a shootout occurred; this was to make it appear as if a shootout had occurred. Brother FS shot J's weapon into the wall many times to make it appear as if a shootout had taken place; Ferdy Sambo became the director behind this murder, including those who designed a fictitious story to cover up the real incident. Then Bharada Eliezer was allegedly the executor who shot Brigadier J, which was carried out on orders from Ferdy Sambo. There were at least three roles played by Ferdy Sambo in this case, including 1).The first role played by Ferdy Sambo was to order the murder of Brigadier J. He ordered the suspect, Bharada E, to shoot Bharata J at his official residence at the Police Complex, Duren Tiga, South of Jakarta 2).The second role is to kill Brigadier J; 3).The third role is to design scenarios as if there was shooting action. Based on the results of the investigation, the four suspects were suspected of committing criminal acts following Article 340 of the Criminal Code on premeditated murder, a subsidiary of Article 338 of the Criminal Code on murder, and Junction Articles 55 and 56 of the Criminal Code on conspiracy. The threat of the death penalty, life imprisonment, or a maximum of 20 years in prison. In addition to criminal matters, Ferdy Sambo's actions are suspected of violating the Police's professional code of ethics. He is suspected of having behaved unprofessionally in handling the scene of the death of Brigadier J. along with 31 other police personnel who are currently being investigated for: 1).Violating Polri's professional ethics, 2). Obstructing the investigation process by eliminating evidence such as CCTV footage and autopsy process; 3). Committing unprofessional actions when handing over Brigadier j's body to the family in Jambi. As a result of this action, the Police locked up 11 officers in a special place related to the death of Brigadier J. So far, 11 officers have been locked up in special placements to undergo the provost's examination process.